Leadership: Validation of a Self-Report Scale: Comment on Dussault, Frenette, and Fernet (2013). Issue 2 (October 2014) - Chakrabarty, Subhra
In a recent study, Dussault, Frenette, and Fernet (2013) developed a 21-item self-report instrument to measure leadership based on Bass's (1985) transformational/transactional leadership paradigm. The final specification included a third-order dimension (leadership), two second-order dimensions (transactional leadership and transformational leadership), and a first-order dimension ( laissezfaire leadership). This note focuses on the need for assessing convergent and discriminant validity of the scale, and on ruling out the potential for common method bias.